2017
DOI: 10.3389/fvets.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Residual Spinal Cord Compression Following Hemilaminectomy and Mini-Hemilaminectomy in Dogs: A Prospective Randomized Study

Abstract: The aim of this study was to compare the reduction of spinal cord compression after surgical treatment of dogs with acute thoracolumbar intervertebral disc (IVD) extrusion achieved using hemilaminectomy versus mini-hemilaminectomy techniques. This was a prospective randomized study with client-owned dogs presented with acute IVD extrusion that were allocated to surgical treatment using hemilaminectomy (n = 15) or mini-hemilaminectomy (n = 15) techniques. Plain and intravenous-contrast computed tomography was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Few studies provide direct comparisons of 1 surgical technique to another. 13,[81][82][83][84] Descriptions of the various techniques and their associated benefits and complications have been summarized previously. 85 In addition, several authors recently have reported minimally invasive techniques to address intervertebral disc herniation in dogs.…”
Section: Surgerymentioning
confidence: 99%
“…Few studies provide direct comparisons of 1 surgical technique to another. 13,[81][82][83][84] Descriptions of the various techniques and their associated benefits and complications have been summarized previously. 85 In addition, several authors recently have reported minimally invasive techniques to address intervertebral disc herniation in dogs.…”
Section: Surgerymentioning
confidence: 99%
“…Bei chronischem thorakolumbalem BSV kann auch eine laterale Korpektomie in Betracht gezogen werden, die im Vergleich zur Hemilaminektomie das Risiko iatrogener Rückenmarksschädigung und Sinusblutung minimiert [17], deren Erfolg allerdings stärker von der Erfahrung des Operateurs abhängt [24]. Die Minihemilaminektomie stellt durch ihre geringe Invasivität eine weitere schonende Methode dar, die eine erheblich stärkere Dekompression für das Rückenmark schafft als die Hemilaminektomie [32]. Im Fall zervikaler BSV ist der ventrale Slot aufgrund der schnellen Durchführbarkeit die Methode der Wahl und findet am häufigsten Anwendung [30] [33].…”
Section: Einleitung Und Zielsetzungunclassified
“…Dies steht konträr zum Ergebnis der Studie von Bull et al [8], die bei größeren Hunden eine längere Rekonvaleszenzzeit feststellten als bei kleineren Hunden. [32]. Eine erhöhte Rezidiv rate konnte weder in Abhängigkeit von den Rassengruppen noch den unterschiedlichen Gewichtsklassen nachgewiesen werden.…”
Section: Auswertung Postoperativer Datenunclassified
“…A mini-hemilaminectomy (Images 1 and 2), however, preserves the articular facet joint and only removes the pedicle, described as for a hemilaminectomy ventral to the articular facet (Lubbe, Kirberger & Verstraele 1994 ). Studies have observed residual spinal cord compression post-operatively when a mini-hemilaminectomy was compared with a hemilaminectomy (Huska et al 2014 ; Svensson et al 2017 ). A recent study has however contraindicated this by indicating less residual disc material with a mini-hemilaminectomy compared with a hemilaminectomy (Svensson et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have observed residual spinal cord compression postoperatively when a mini-hemilaminectomy was compared with a hemilaminectomy (Huska et al 2014;Svensson et al 2017). A recent study has however contraindicated this by indicating less residual disc material with a minihemilaminectomy compared with a hemilaminectomy (Svensson et al 2017). Hemilaminectomy has however been shown in mechanical studies to increase the range of motion of the vertebral column by 11%; this has been put forward as a cause of instability in dogs recovering from decompressive surgery of the spinal cord (Hill, Lubbe & Guthrie 2000).…”
Section: Introductionmentioning
confidence: 99%